Nutritional and fermentation parameters of Xaraés grass silage produced with bacterial additive - Erickson Tiago Pinheiro da Silva; Katia Cylene Guimarães; Karolyna Oliveira Marques; Thony Assis Carvalho; Patricia Antonio; Marcos Ires Rodrigues Vieira Junior (Acta Scientiarum. Animal Sciences, 2014)
The use of bacterial additives in forage silages with low content of dry matter prevents undesirable fermentation and reduces losses by gases (PG) and effluents (PE) during the ensiling process. This study aimed to evaluate the fermentation parameters, chemical composition and in vitro digestibility of silage of Urochloa brizantha cv. Xaraés produced with bacterial additive. The inoculant contained the following strains: Propionibacterium acidipropionici + Lactobacillus plantarum; Lactobacillus buchnari; Propionibacterium acipropionici + commercial enzymes and Lactobacillus plantarum and Pediococcus pentosaccus, at 0, 25, 50, 75, 100, and 125% of the recommended level for sugarcane (2 g ton-1). The experiment was a completely randomized design with four replications, and six levels of inoculant (0, 25, 50, 75, 100, and 125%). There was a quadratic relationship between the inoculant addition and the levels of pH, PE, DMIVD, NDF, ADF and LIG of the silage. PG and MM increased linearly with the addition of inoculant. The N-NH3, DM, CP, CEL, HEM and EE were not affected by the inoculant. Bacterial additive at 50% provided increased DMIVD. Appropriate values were found for pH and NH3.